Autoimmune paraneoplastic syndromes associated to lung cancer: A systematic review of the literature: Part 5: Neurological auto-antibodies, discussion, flow chart, conclusions. (September 2017) - Sculier, Claudine; Bentea, Georgiana; Ruelle, Lucien; Grigoriu, Bogdan; Coureau, Michelle; Gorham, Julie; Sideris, Spyridon; Holbrechts, Stéphane; Lafitte, Jean-Jacques; Meert, Anne-Pascale; Durieux, Valérie; Berghmans, Thierry; et al.
Abstract: The development of new immune treatment in oncology and particularly for lung cancer may induce new complications, particularly activation or reactivation of auto-immune diseases. In this context, a systematic review on the auto-immune paraneoplastic syndromes that can complicate lung cancer appears useful. This article is the last of a series of five and deals mainly with onconeural antibodies involved in neurological paraneoplastic syndromes and provides the final discussion.